Activation of presynaptic GABAB receptors enables sustained transmission at high rate of stimulation in cholinergic olivocochlear-hair cell synapses - Wedemeyer, Carolina (2014)
During development, medial olivocochlear (MOC) neurons transiently innervate cochlear inner hair cells (IHCs). Although acetylcholine is the main neurotransmitter at this synapse, an abundant GABA innervation is also present. Electrical stimulation of efferent fibers triggers the release of acetylcholine, but also activates presynaptic GABAB receptors, that in turn reduce the amount of ACh release. The mechanism of action of GABA is through the inhibition of P/Q type Ca2+ channels. We are now studying the consequences of GABAB-mediated inhibition in the short-term plasticity properties of this synapse. Inhibitory synaptic currents (IPSC) were recorded in IHCs of acutely isolated organs of Corti at P9-P11 while MOC fibers were electrically stimulated. In control conditions, 15 pulses applied at high frequency (50 or 100 Hz) resulted in a progressive decrease in IPSC amplitudes. At 50 Hz, the depression rate was 32% whereas it increased to 53% at 100 Hz. At low-frequency (10 Hz), the specific GABAB agonist, baclofen, reduced the amplitude of IPSCs throughout the train. However, at higher stimulus rates, IPSCs were always larger than controls with a maximal enhancement of 43% for the last IPSC of the train at 100 Hz. These results suggest that by reducing synaptic depression, activation of GABAB receptors would enable sustained transmission during high-frequency stimulation at the MOC-inner hair cell synapse.